The Realization of Ideational Meaning in Indonesian Folktales - Abdul Halim Mahmud (Passage, 2019)
The present study investigates how ideational meaning is realized in Indonesian folktales. Three folktales from three different regions were used as the data, namely Malin Kundang, Timun Mas, and Sangkuriang. The analyses were conducted by using the Systemic Functional Linguistics theory proposed by Halliday (1985) as the theoretical framework, mainly focusing on the concept of transitivity. The findings show that material process, relational process, and verbal process are dominantly used in the folktales. There are also the two most identified participants in the folktales, namely goal and actor. The circumstance of time and the circumstance of place become the most frequent circumstances in the folktales. Moreover, the context of situation influences the use of language in the folktales. There are some attributes attached to the subject matters being conveyed, which are about family issues and supernatural events. Lastly, the main participants in the folktales have a variety of attributes representing themselves and their relationships. In conclusion, the findings demonstrate that Indonesian folktales used in this study reflect Indonesian’s cultural beliefs and way of life. Keywords: ideational meaning; transitivity; context of situation; systemic functional linguistics